Species of Hemiptera-Heteroptera associated to Opuntia spp. and Nopalea spp. in the Mexican Chihuahuense Desert - Rocha Flores, Rosa Gloria; García Martínez, Oswaldo; Villarreal Quintanilla, José Ángel; Sánchez Peña, Sergio Rene (Revista Mexicana de Ciencias Agrícolas, 2017)
The Chihuahuense Desert has an approximate extension of 507 000 km2 where a vast diversity of organisms is expressed, with a good number of Hemiptera-Heteroptera species present. In this study we determined species of the group in the Chihuahuense Desert, covering six states of the Mexican Republic of this important ecosystem. 10 families of Heteroptera were identified, among them Miridae and Coreidae, in the latter the first report is highlighted of Chelinidea vittiger aequoris Uhler, 1963 for this ecosystem and Cimicidae and Reduviidae, which have medical-veterinary importance.